Treatment patterns among patients with malignant pleural mesothelioma: An Italian, population‐based nationwide study. Issue 6 (4th May 2020) - Trama, Annalisa; Proto, Claudia; Signorelli, Diego; Garassino, Marina C.; Lo Russo, Giuseppe; Ganzinelli, Monica; Prelaj, Arsela; Mensi, Carolina; Gangemi, Manuela; Gennaro, Valerio; Chellini, Elisabetta; Caldarella, Adele; et al.
Abstract: Background: Malignant pleural mesothelioma (MPM) is a rare cancer with a poor prognosis. Centralization of rare cancer in dedicated centers is recommended to ensure expertise, multidisciplinarity and access to innovation. In Italy, expert centers for MPM have not been identified in all regions. We aimed to describe the treatment patterns among MPM patients across different Italian regions and to identify factors associated with the treatment patterns across the regions. Methods: We performed an observational study on a random sample of 2026 MPM patients diagnosed in 2003–2008. We included 26 population‐based registries covering 70% of the Italian population. To identify factors associated with treatment patterns, across the different regions, we fitted a multinomial logistic regression model adjusted by age, sex, stage, histology and hospital with thoracic surgical department. Results: MPM patients mostly received chemotherapy alone (41%) or no cancer‐directed therapy (36%) especially the older patients. The first course of treatment for MPM patients differed across regions. Patients from Piedmont, Liguria and Campania were more likely to receive no cancer‐directed therapy; those living in Tuscany and Sicily were more likely to get surgery; patients from Marche and Lazio were more likely to receive chemotherapy. These differences were not explained by age, sex, stage, histology and availability of a thoracic surgery department. Conclusions: There is limited expertise available and lack of a network able to maximize the expertise available may contribute to explaining the results of our study. Our findings support the need to ensure the appropriate care of all MPM patients in reorganizing the health care services. Key points: Significant findings of the study: MPM patients mostly received chemotherapy alone or no cancer‐directed therapy especially the older patients. The first course of treatment for MPM patients differed across Italian regions. What this study adds: Differences in MPM clinical management are not explained by the age, stage, histology nor by the availability of a thoracic surgery department. Limited expertise for MPM contribute to explaining the unequal access to appropriate care for MPM patients in Italy.